INFLUENCE OF WORK ENVIRONMENT, WORK-LIFE BALANCE, AND LEADERSHIP ON EMPLOYEE PERFORMANCE IN ISLAMIC BUSINESS PERSPECTIVE - Serliana Yulia; Ahmad Zuliansyah; Yeni Susanti (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to analyze the influence of work environment, work-life balance, and leadership on employee performance from the perspective of an Islamic business. The underlying phenomenon is the importance of creating a conducive work environment, maintaining a balance between work and personal life, and applying effective leadership to enhance employee performance in line with the principles of Islamic business. The research employed a quantitative approach using multiple linear regression analysis and a saturated sampling technique, in which all employees were included as samples. Data were collected through questionnaires distributed to 40 respondents who are employees at the research site. The findings reveal that both partially and simultaneously, the variables of work environment, work-life balance, and leadership have a positive and significant effect on employee performance. From the perspective of Islamic business, these factors align with values such as ihsan (striving for the best quality of work), amanah (responsibility), and adl (justice), which foster blessings and productivity in the workplace. The conclusion emphasizes that implementing a comfortable work environment, ensuring proper work-life balance, and practicing fair and wise leadership not only improve employee performance but also contribute to establishing a work climate consistent with Sharia principles.